Laparoscopic Umbilical Hernia Repair: Technique Paper. (16th September 2012) - Abhishek, V.; Mallikarjuna, M. N.; Shivaswamy, B. S.
Abstract : Objective . Laparoscopic umbilical hernia repair has largely replaced open method. The purpose of this study was to document the laparoscopic umbilical hernia repair using two port, combined herniorrhaphy with intraabdominal mesh fixation with transabdominal absorbable suture technique and demonstrate that it is feasible, efficient, and safe. Methods . Thirty-two patients with umbilical hernia underwent laparoscopic repair by combined herniorrhaphy and intraabdominal mesh. Two-port technique was used and the umbilical defect was closed using transabdominal PDS suture, composite polypropylene, and PTFE mesh was placed intra-bdominally and fixed to abdominal wall using transabdominal PDS suture. Results . Thirty-two patients underwent laparoscopic repair. The operating time ranged from 45 min to 100 min (mean 64 min). Early postoperative complication was seen in five patients with two having ileus for 4 days and one patient each developed urinary retention, wound infection and seroma. Late postoperative complication was seen in 6 patients with five complaining of persistent abdominal pain which resolved without treatment and one case of keloids at port sites. None of the patients developed chronic pain or had recurrence over the follow-up period. Conclusion . Laparoscopic umbilical hernia repair with combined herniorrhaphy and intraabdominal mesh fixation using absorbable sutures offers an efficient, safe, and effective repair for umbilical hernia.